Extraction liquide-liquide du cobalt(II) par la N-(2-hydroxybenzylidene) aniline - Aidi, Amel; Barkat, Djamel (Journal of Applied Engineering Science & Technology, 2018)
The liquid–liquid extraction of cobalt(II) from sulfate medium with N-(2-hydroxybenzylidene)aniline is studied with the following parameters: pH, concentration of the extractant and the nature of diluent. The solvent extraction of cobalt(II) in different diluents leads to third phase formation. The stoichiometry coefficients of the extracted complexes are determined by the slope analysis method. The extaction constants are evaluated for the different diluents. The extraction is better in the following order: cyclohexane > toluene > chloroform.